The Influence Analysis Of Discovery Learning Model On Students' Cognitive Ability - Kriswanto Kriswanto; Rahmah Evita Putri (Department of Science Education, 2021)
This research was motivated by the still low learning outcomes of students, especially in cognitive abillities. Discovery Learning model is one of the learning model that can be used to increase students cognitif ability. The aim of this research is to analyze the external factors of Discovery Learning models that effect the student cognitive abilities, from several research articles. This is an expost facto research with descriptive qualitative approach and documentation as the teachnique to collect the data. The sample used in this research were articles (at least 3) relating to the used of the Discovery Learning model on students' cognitive abilities with a minimum journal level of Q3. The data analysis technique consists of several steps, there were, data reduction, data display, and verification. The result shows there were several external factors that affect the students' cognitive abilities in the application of the Discovery Learning learning model, such as the learning environment, learning media, and providing stimulus.